Implementasi Pembelajaran Berbasis Proyek untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Matematika di SD Negeri Pinedapa - Manawia H Lapase (Jurnal Paedagogy, 2021)
The purpose of this study was to improve mathematics learning outcomes with the subject of calculating the area of a flat shape using a project-based learning model for grade VI students of SD Negeri Pinedapa. This research uses classroom action research which is carried out in 3 cycles. Each cycle is carried out in 4 (four) stages, namely planning, implementing, observing, and reflecting. The instruments used in this research were tests, observation, and documentation. The data analysis technique used descriptive qualitative and quantitative analysis. The research results from each cycle increased. Based on the results of the cycle III test, it was found that the average learning outcome was 80.31 out of 32 students who scored 70-85 there were 21 students, and the range 86-100 had 11 students. The conclusion of this study is that through the use of a project-based learning model it can improve students' mathematics learning outcomes on the subject of calculating the area of a flat shape in class VI SD Negeri Pinedapa.